Influence of Irrigation Water Quality on Exchangeable Sodium Percentage in a Sodic Soil - Rawat, B S; Singh, T A (Annals of Arid Zone, 2016)
Laboratory leaching studies with a ’Sodic’ soil from Aligarh using different quality irrigation waters revealed that more efficient leaching was accomplished with waters of high electrolyte concentrations and low or very low sodium adsorption ratio (SAR) values. To remove a given amount of salt larger amounts of high SAR waters will be required as compared to Low SAR waters. Equilibrium conditions were attained between soil and the effluent solution in the layers but not in the lower layers.